Antecedents and determinants of the decision to centralize the procurement function - Sousa, Pedro Carvalho Martins Guedes de (2024)
The research focuses on identifying key factors that drive companies to centralise procurement. Using a comprehensive literature review and a survey of procurement experts, the study develops and tests a conceptual framework that categorizes determinants into three main dimensions: supply side factors, internal factors, and market side factors. The survey findings suggest a significant influence of these factors on the decision to centralise procurement, with differences observed across company sizes and respondent experience levels. This research contributes to academic knowledge and practical applications in procurement strategy, providing insights to help firms optimize procurement functions in a changing global environment.